Linguistic Means of Conveying Persuasion in the Advertising Discourse of the Danube Region - Soroka, Tetiana (Journal of Danubian Studies and Research, 2024)
Persuasion should be understood as verbal and nonverbal influence on the human psyche, which is perceived without critical evaluation, but changes its psychoemotional and physiological state. Persuasive influence is carried out during the interaction of the persuader (subject of persuasion) and the sugerend (object of persuasion), and the success of such interaction depends on both their personal qualities and situational factors. The analysis of the phenomenon of persuasion allowed us to present the definition of persuasive discourse as a purposeful communicative action in order to influence the subconscious of the addressee to change one’s psychoemotional and physiological state, which is a set of process and result and includes both extra-linguistic and linguistic components. Persuasion is an integral part of both everyday communication and professional discourse. It is widely used in such a communicative sphere as advertising discourse. Mass media are a powerful source of influence on the subconscious of a large audience, and persuasive technologies are usually used here for advertising purposes. In order to influence the addressee, specialists in the field of advertising use not only individual linguistic techniques to enhance persuasive influence (emotionally-coloured lexical units, tropes, repetitions, enumerations, parcelling, rhyme, paronymic attraction), but also ready-made persuasive texts in which the object of advertising is encoded.